Trade, trust and institutions - Shu Yu; Jakob de Haan; Sjoerd Beugelsdijk (Center for Economic Studies and ifo Institute (CESifo), 2011)
To investigate the relation between trust and formal institutions, we analyze bilateral trade patterns in a sample of 16 European countries between 1996-2009. Trust in trading partners has a significant positive effect on bilateral trade. However, our results suggest that trust and formal institutions are substitutes, as the positive effect of trust on trade is conditional on the quality of formal institutions. When the institutional quality of the importing country increases, the effect of trust on trade decreases, and eventually becomes insignificant. The decline in the effect of trust on trade is less when the exporting country's institutional quality improves.
Keywords: F10; Z10; K40; 330; trust; international trade; institutional quality